Novel Androstenetriol Interacts with the Mitochondrial Translocator Protein and Controls Steroidogenesis - Midzak, Andrew (American Society for Biochemistry and Molecular Biology, 2011)
Steroid hormones are metabolically derived from multiple enzymatic transformations of cholesterol. The controlling step in steroid hormone biogenesis is the delivery of cholesterol from intracellular stores to the cytochrome P450 enzyme CYP11A1 in the mitochondrial matrix. The 18-kDa translocator protein (TSPO) plays an integral part in this mitochondrial cholesterol transport. Consistent with its role in intracellular cholesterol movement, TSPO possesses a cholesterol recognition/interaction amino acid consensus (CRAC) motif that has been demonstrated to bind cholesterol. To further investigate the TSPO CRAC motif, we performed molecular modeling studies and identified a novel ligand, 3,17,19-androsten-5-triol (19-Atriol) that inhibits cholesterol binding at the CRAC motif. 19-Atriol could bind a synthetic CRAC peptide and rapidly inhibited hormonally induced steroidogenesis in MA-10 mouse Leydig tumor cells and constitutive steroidogenesis in R2C rat Leydig tumor cells at low micromolar concentrations. Inhibition at these concentrations was not due to toxicity or inhibition of the CYP11A1 enzyme and was reversed upon removal of the compound. In addition, 19-Atriol was an even more potent inhibitor of PK 11195-stimulated steroidogenesis, with activity in the high nanomolar range. This was accomplished without affecting PK 11195 binding or basal steroidogenesis. Finally, 19-Atriol inhibited mitochondrial import and processing of the steroidogenic acute regulatory protein without any effect on TSPO protein levels. In conclusion, we have identified a novel androstenetriol that can interact with the CRAC domain of TSPO, can control hormonal and constitutive steroidogenesis, and may prove to be a useful tool in the therapeutic control of diseases of excessive steroid formation.